Review on Composite Structural Health Monitoring Based on Fiber Bragg Grating Sensing Principle - 邱野 王全保 赵海涛 陈吉安 王曰英 (Shanghai jiao tong da xue xue bao, 2013)
Fiber Bragg grating （FBG） based sensors offer important advantages over traditional instrumentation with regards to real-time structural health monitoring （SHM） of composite materials and structures in recent years. FBG sensors, integrated into existing structures or embedded into new ones, have played a major role in assessing the safety and integrity of engineering structures. In this paper, a review on the latest research of the FBG-based SHM technique for composite field is presented. Firstly, the FBG sensing principle is briefly discussed and FBG and several other optical fiber sensors （OFSs） for SHM are performance-compared. Then, several examples of the use of FBG sensors in composite SHM are illustrated, including those from the field of cure monitoring, civil engineering, aviation, aerospace, marine and offshore platform. Finally, some existing problems are pointed out and some proposals for further researches are provided.